Royal control of the church in the twelfth-century kingdom of Sicily - Loud, G. A. (Studies in church history, 1982)
For the king, after the fashion of tyrants, had reduced the church in his kingdom to slavery’. So John of Salisbury stigmatized king Roger II of Sicily. He continued that ‘instead of allowing any freedom of elections [Roger] named in advance the candidate to be elected, so disposing of all ecclesiastical offices like palace appointments’. This picture has been accepted by modern historians with very few reservations. To quote the standard history of the Norman kingdom of Sicily of Ferdinand Chalandon, still unrivalled after more than seventy years, ce qui caractérise la situation des évêques a l’époque normande, c’est la dépendance absolue où ils se trouvent vis-à-vis du roi.